2020
DOI: 10.3389/fnagi.2020.00236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mini-Mental State Examination and the Montreal Cognitive Assessment for Predicting Post-stroke Cognitive Impairment During the Acute Phase in Chinese Minor Stroke Patients

Abstract: Objective: To assess the value of the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA) during acute phase in predicting post-stroke cognitive impairment (PSCI) at 3-6 months. Methods: We prospectively recruited 229 patients who had suffered their first-ever ischemic stroke. PSCI was determined in 104 of these patients by a comprehensive neuropsychological battery performed at 3-6 months. Receiver operating characteristic (ROC) curve analysis was then performed to compare the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 34 publications
1
31
0
1
Order By: Relevance
“…Experienced neurological physicians, blinded to the baseline characteristics of the patients, evaluated the cognitive function of the patients using the Chinese version of the MMSE (27) at 1 month after stroke. The MMSE has been translated into Chinese and was validated for reliability and validity as a screening tool for cognitive impairment in the Chinese stroke population (28). The MMSE scores range from 0 to 30, with higher scores indicating better performance.…”
Section: Outcome Assessment and Follow-upmentioning
confidence: 99%
“…Experienced neurological physicians, blinded to the baseline characteristics of the patients, evaluated the cognitive function of the patients using the Chinese version of the MMSE (27) at 1 month after stroke. The MMSE has been translated into Chinese and was validated for reliability and validity as a screening tool for cognitive impairment in the Chinese stroke population (28). The MMSE scores range from 0 to 30, with higher scores indicating better performance.…”
Section: Outcome Assessment and Follow-upmentioning
confidence: 99%
“…Four studies that compared the MMSE and MoCA showed equivalent sensitivity and specificity to identify PSCI [47][48][49][50]. However, only two studies [47,49] met the detection accuracy standard of 80% sensitivity and 60% specificity, as suggested by Stolwyk et al [14].…”
Section: Detection Accuracy Of the Mmse And Mocamentioning
confidence: 94%
“…Detection accuracy improved after a processing speed test was added in the ROC analysis (sensitivity = 97-98%, specificity = 76-78%). Likewise, Zhu et al [50] reported poor sensitivity for both tests (MMSE = 68%, MoCA = 64%). Studies that found equivalent detection accuracy for the MMSE and MoCA also recruited older patients (see Table 1).…”
Section: Detection Accuracy Of the Mmse And Mocamentioning
confidence: 94%
See 2 more Smart Citations